2021
DOI: 10.21203/rs.3.rs-280664/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Multidimensional Model of Healthy Ageing: Proposal and Evaluation of Determinants Based on a Population Survey in Ecuador.

Abstract: Background: Healthy ageing is a complex construct, which involves multiple dimensions. The objective of this study was to design a multidimensional model of healthy ageing and to identify its determinants from national data in Ecuador. Methods: A cross-sectional analytical study was carried out from the National Survey of Health and Well-being of the Older Adult, 2010. Sample was 1797 adults aged 65 years or more (sample expanded to 898,152). A multidimensional model was designed based on the domains involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
(40 reference statements)
0
3
1
Order By: Relevance
“…Unlike our fndings, a number of studies reported higher levels of SA in female participants [30,40]. Te study of Rivadeneira et al [35] in Ecuador found lower levels of SA in female participants. Similarly, Roberts et al [41] found lower levels of SA in females in Canada.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…Unlike our fndings, a number of studies reported higher levels of SA in female participants [30,40]. Te study of Rivadeneira et al [35] in Ecuador found lower levels of SA in female participants. Similarly, Roberts et al [41] found lower levels of SA in females in Canada.…”
Section: Discussioncontrasting
confidence: 86%
“…Other studies in China and Taiwan also reported a negative relationship between SA perception and age [36,37]. Tese fndings may be explained with reference to chronic diseases associated with aging and the negative efects of aging on the functional capacities of older adults [35].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations